Gods profound and mysterious providence : as revealed in the generalogy of Jesus Christ from the time of David to the exile in Babylon / Rev. Abraham Park - PARK, Abraham, Rev. (Periplus Edition, 2011)
351 hlm. : ilus. ; 24 cm [3 eks.]